Einstein’s Vision of Time and Infinite Universe without Singularities: The End of Big Bang Cosmology - Sorli, Amrit Srecko (JOURNAL OF ADVANCES IN PHYSICS, 2020)
Cosmology should be built on falsifiability, bijectivity, and experimental data. Speculations are not allowed. NASA has measured universal space has Euclidean shape, which means universal space is infinite in the volume. Einstein’s vision on time as the sequential order of events running in space has bijective correspondence with the physical reality and means that the universe does not run in some physical time; it runs only in space, which is time-invariant. In this timeless universe, there is no singularity of the beginning, there is no singularity inside of black holes. The energy of the universe is non-created, its transformation is eternal without the beginning and without the end.